A pilot study examining Toronto-area family physician perspectives on thyroid neoplasm evaluation - Arjun Kundra; David P. Goldstein; Kimberly Wintemute; Sangeet Ghai; Richard W. Tsang; Karuna Gupta; Donatus R. Mutasingwa; Jeff Weissberger; Ella Huszti; Patrick Brown; Huan Jiang; Anna M. Sawka (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Objective The incidence of thyroid cancer (TC) is known to be very high in the Greater Toronto Area of Ontario, Canada. We performed a pilot survey study examining Toronto-area family physician (FP) perspectives on thyroid neoplasm evaluation (i.e. thyroid nodules [TNs] or thyroid cancer [TC]) in this region, to explore for potential factors leading to overdiagnosis. Methods We performed a cross-sectional mail-out written survey of a random sample of 300 FPs in active practice in the Greater Toronto Area (Markham and Brampton). Results The overall response rate was 22.3, 95% confidence interval (CI) 18.0, 27.4% (67/300); the effective response rate was 19.9, 95% CI 15.7, 24.9% (58/291), after excluding 6 FPs that reported TN evaluation was outside their scope of practice and three FPs with an invalid mailing address. There were no missing responses to questions. The demographic characteristics were as follows: 58.6% (34/58) from Markham, 55.2% (32/58) were female, 58.6% (34/58) were in practice > 10 years, and 32.8% (19/58) affiliated with a University. All FPs reported easy access to thyroid ultrasound (TUS). About half of FPs were concerned about overdiagnosis of TC and most did not believe that there was any TC survival advantage with routine screening TUS. Although appropriate indications for TUS were endorsed by most respondents (e.g. palpable TN, incidental TN on other imaging), inappropriate recommendations were observed in a third of FPs (19/57) who recommended TUS for abnormal thyroid blood tests about half of FPs (30/56) who endorsed biopsy of sub-centimeter nodules. About half of FPs (31/58) reported that their patients sometimes request medically unnecessary TUS. Conclusion There are likely multiple complex factors leading to potential overdiagnosis of TC in primary care, including some physicians’ knowledge gaps about appropriate indications for TN investigations as well as patients’ requests and expectations.